38.5k views
5 votes
Solve for x
-2(4x-5)+2x+4=26

User Nhu Trinh
by
5.1k points

2 Answers

5 votes

Answer:

X= -2

Explanation:

Step 1: Simplify both sides of the equation.

−2(4x−5)+2x+4=26

(−2)(4x)+(−2)(−5)+2x+4=26(Distribute)

−8x+10+2x+4=26

(−8x+2x)+(10+4)=26(Combine Like Terms)

−6x+14=26

−6x+14=26

Step 2: Subtract 14 from both sides.

−6x+14−14=26−14

−6x=12

Step 3: Divide both sides by -6.

−6x

−6

=

12

−6

x=−2

Answer:

x=−2

User Nash
by
5.5k points
1 vote

We can use the distribution property:

-2 (4x - 5) + 2x + 4 = 26

Move like terms to one side and distribute:

-2 (4x - 5) + 2x + 4 = 26

-8x + 10 + 2x + 4 = 26

-8x + 2x = 26 - 10 - 4

Simplify:

-6x = 12

Solve:

6x = -12

x = -2

User Linbo
by
4.6k points